2010
DOI: 10.1590/s1806-37132010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de curto prazo do tiotrópio nos portadores de DPOC em tratamento com β2-agonista

Abstract: Objective: To evaluate the short-term impact of tiotropium in patients with severe or very severe COPD who complain of dyspnea despite being currently treated with other bronchodilators. Methods: A prospective study including patients with severe or very severe COPD and complaining of dyspnea at rest or on minimal exertion. Every 15 days, the bronchodilator treatment regimen was altered, from salmeterol to tiotropium to salmeterol+tiotropium. At the end of each regimen, pulmonary function tests and the six-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Tiotropium is the most studied pharmacological agent, and COPD studies have indicated satisfactory results, including a reduction in the number of exacerbations, an improvement in quality of life and an increase in the FEV1 (99). There is no evidence that supports the superiority of LAMAs over LABAs; however, the combination of these drugs may be used with an additive effect in patients with accentuated lung function or significant functional limitations (100). Recently, the use of tiotropium in asthma has been studied as an alternative in patients with contraindications to the use or in combination with LABAs (101).…”
Section: Introductionmentioning
confidence: 99%
“…Tiotropium is the most studied pharmacological agent, and COPD studies have indicated satisfactory results, including a reduction in the number of exacerbations, an improvement in quality of life and an increase in the FEV1 (99). There is no evidence that supports the superiority of LAMAs over LABAs; however, the combination of these drugs may be used with an additive effect in patients with accentuated lung function or significant functional limitations (100). Recently, the use of tiotropium in asthma has been studied as an alternative in patients with contraindications to the use or in combination with LABAs (101).…”
Section: Introductionmentioning
confidence: 99%
“…Fernandes et al89 evaluated the short-term impact of tiotropium in patients with severe or very severe COPD who complain of dyspnea despite being currently treated with other bronchodilators and claim that the introduction of tiotropium into the treatment of such patients using long-acting beta(2) agonists improves pulmonary function and provides symptomatic relief, as perceived by patients in the short term. They claim that these results, obtained under real life treatment conditions, support the use of the salmeterol+tiotropium combination in specific treatment protocols for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of tiotropium bromide in the treatment of COPD has also been demonstrated in various randomized trials and in a real-life study. (6) The combination of tiotropium bromide, which is a bronchodilator classified as a LAMA, is beneficial in patients with severe and very severe COPD. The use of a LAMA alone as an initial treatment or its association with a LABA is indicated in patients with COPD and moderate obstructive lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exacerbations should be prevented and treated, reducing the number of hospitalizations. (2,5,6) Non-pharmacological and pharmacological treatment is established in accordance with national and international guidelines, (2,7) the pillars of treatment being the use of long-acting bronchodilators. The evolution in the knowledge of the disease and in clinical research resulted in the introduction of new drugs for the treatment of COPD.…”
Section: Introductionmentioning
confidence: 99%